Anticholinergic, antidiabetic and antioxidant activities of cinnamon (cinnamomum verum) bark extracts: polyphenol contents analysis by LC-MS/MS. Issue 1 (1st January 2019) - Gulcin, Ilhami; Kaya, Ruya; Goren, Ahmet C.; Akincioglu, Hulya; Topal, Meryem; Bingol, Zeynebe; Cetin Çakmak, Kader; Ozturk Sarikaya, Sevim B.; Durmaz, Lokman; Alwasel, Saleh
ABSTRACT: Ethanolic (EEC) and aqueous (WEC) extracts of cinnamon ( Cinnamomum verum ) were evaluated for their antioxidant profiles by eight distinguished bioanalytical antioxidant methods. Their inhibitory effects were tested against some enzymes including acetylcholinesterase, butyrylcholinesterase, α-glycosidase and α-amylase, which linked to different diseases. Additionally, the antioxidant properties were determined and polyphenolic compositions of the both extracts were evaluated by LC-MS/MS analysis. According to the LC-MS/MS experiments, thirteen compounds were found in WEC and EEC. Also, p -hydroxybenzoic acid (321.1 mg/kg extract), p -coumaric acid (291.4 mg/kg extract), and pyrogallol (142.4 mg/kg extract) were found to be the most abundant ingredients in the WEC. On the other hand, pyrogallol (264.3 mg/kg extract), ferulic acid (224.7 mg/kg extract) and p -coumaric acid (170.2 mg/kg extract) were found as the most plentiful chemicals in the EEC. For the estimation of the antioxidant capacities of the both extracts (WEC and EEC), DPPH· and ABTS + scavenging activities, as well as Fe 3+ -Fe 2+, and Cu 2+ -Cu + reducing assays were studied. The IC50 values of the WEC and EEC indicated that they were potent effective DPPH· (21. 25 and 15.71 μg/mL) and ABTS + (6.52 and 5.79 μg/mL) scavengers, as well as AChE (221.33 and 110.26 μg/mL), BChE (461.69 and 94.93 μg/mL), α-glycosidase (206.86 and 220.00 μg/mL) and α-amylase (189.86 and 200.86 μg/mL) inhibitors. As a conclusion, both EEC and WEC had rich phenolic contents and demonstrated effective anticholinergic, antidiabetic and antioxidant effects.